The Effect of Visionary Leadership and Lecturer’s Performance on Students’ Achievements - Herdayati Herdayati; Edi Harapan; Tobari Tobari; Asya N Samsonova (INTERNATIONAL JOURNAL OF EDUCATIONAL REVIEW, 2020)
This study aimed at determining how high leadership style and lecturers' performance on students' achievement in STIKes Muhammadiyah Palembang. This study used a quantitative survey by using questionnaire to collect the data. The data were analyzed by using SPSS for Windows. The results obtained indicate that there is no effect of visionary leadership toward students' achievement, but there is an effect of lecturers' performance toward students' achievement. While tested simultanously, the visionary leadership style and lecturers 'performance toward students' achieved had significant effect.